A possible role for IL-17A in establishing Th2 inflammation in murine models of atopic dermatitis - Dhingra, Nikhil (2014)
Atopic dermatitis (AD) is associated with the effects of Th2 and Th22 cytokines. Recent studies, however, have also implicated Th17 in acute AD. Functional studies of Th2 and Th22 cytokines revealed their roles in generating AD’s molecular changes; IL-17A’s role has yet to be defined. In this issue, Nakajima et al. (2014) begin to define that role by demonstrating IL-17A’s ability to induce Th2 inflammation in acute disease.